2021
DOI: 10.1016/j.jadohealth.2021.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Number of Adolescents/Young Adults Seeking Eating Disorder-Related Care

Abstract: The COVID-19 pandemic has led to the development and worsening of eating disorder (ED) symptoms in adolescents and young adults. In order to examine COVID-19-related trends in ED care-seeking at our institution. Methods: We used interrupted time series regression to examine pre-and postpandemic monthly summary data of the following: (1) ED-related inpatient admissions for medical stabilization; (2) ED-related hospital bed-days; (3) completed outpatient ED assessments; and (4) ED outpatient care-related inquiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
94
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 16 publications
11
94
0
4
Order By: Relevance
“…These results highlight an increase in ED, and support the results of a recent study conducted among students of the same university in the past decade years which showed that one in three women and one in seven men had an ED [24]. Lin et al [23] demonstrated the increasing volumes of inpatient and outpatient young adults with eating disorders since the COVID-19 pandemic began. Bulimia remained the most prevalent ED as before the COVID-19 pandemic [24].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results highlight an increase in ED, and support the results of a recent study conducted among students of the same university in the past decade years which showed that one in three women and one in seven men had an ED [24]. Lin et al [23] demonstrated the increasing volumes of inpatient and outpatient young adults with eating disorders since the COVID-19 pandemic began. Bulimia remained the most prevalent ED as before the COVID-19 pandemic [24].…”
Section: Discussionsupporting
confidence: 85%
“…The COVID-19 pandemic has also led to anxiety and depression symptoms among university students [19,20] which are well known to be associated with ED [21,22]. The Lin study [23] highlights how the COVID-19 pandemic has hampered the ability to promptly identify and treat young people with eating disorders. Recently we highlighted a sharp increase in ED in 2021 compared to the previous 10 years [24].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study at the Perth Children's Hospital in Australia found a 104% increase in the number of anorexic patients under the age of 16 admitted for somatic stabilization (severe undernutrition, risk of cardiovascular distress) in comparison with previous years [ 59 ]. Similar results were obtained in the USA showing a significant increase in the use of medical care for eating disorders after the implementation of restrictions due to the COVID-19 crisis among a population aged 8 to 26 years [ 60 ]. The explanatory hypothesis advanced by the authors is that health measures of social restriction have led to the loss of several protective factors and promoted comorbid symptoms/pathologies.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, in one study (14%), 26% of parents disagreed that their child was coping during the pandemic (Shaw et al, 2021 ), and two studies (28%) reported parents to hold favorable attitudes toward the transition to online treatment for their child (Brothwood et al, 2021 ; Stewart et al, 2021 ). One study (14%) also found evidence that parent inquiries to a specialized eating disorder program increased during the pandemic period relative to pre‐pandemic periods (Lin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%